Reasoning Training in the ACTIVE Study: How Much Is Needed and Who Benefits?. (December 2013) - Willis, Sherry L.; Caskie, Grace I. L.
Objective: To characterize change through 5-year follow-up, associated with training, booster, adherence, and other characteristics.Methods: Sample included all individuals randomly assigned to reasoning training (N = 699). Piecewise latent growth modeling was used to examine trajectory of performance on outcome measures.Results: Training resulted in improved reasoning performance through Year 5. A significant third annual booster effect was one-half the size of the training effect. Training adherence resulted in greater training effects. Higher education, Mini-Mental State Exam (MMSE), better health, and younger age related to higher baseline performance. Higher MMSE was related to larger training effects, larger linear slopes, and smaller booster effects. Significant functional outcomes included a training effect for complex reaction time (CRT), and first annual booster effects for the CRT and observed tasks of daily living.Discussion: Initial training gain was comparable with magnitude of age-related cognitive decline over 5 years with no training. Neither age nor gender predicted training or booster effects, indicating the generality of training effects across age (65-90 years).